Estudio de coordinación de protecciones en redes eléctricas de distribución con generación distribuida. - Pilataxi Freire, Luis Gregorio (2021)
Electrical Distribution Systems were created so that the power flow flows in a single direction, being generally of radial topology, while the insertion of Distributed Generation changes the system variables, the short-circuit currents and the power flows vary in their structure. In this research project, the study of the coordination of protections in electrical distribution networks was carried out with the integration of Distributed Generation to the system. For this reason, the IEEE 15-bar radial distribution system was used, being considered as a base case for the simulation in the DIgSILENT Power Factory software, with the values obtained from short-circuit in the system bars, the respective protection coordination was developed. For the four proposed GD insertion scenarios, it was necessary to modify the TAP and DIAL variables so that they comply with the coordination of protections of the radial distribution system with the presence of the Distributed Generation